Qaul Al-Mukhtār Al-Nawawī sebagai Pendapat Alternatif Muslim Nusantara - Kudhori, Muhammad (Fakultas Syariah IAIN Purwokerto, 2018)
The spreading of Syafi’ite school of law in Indonesia until now has a long history in the process of Islamic transmission in the country. Islam entered into Indonesian archipelago through the merchants in the seventh century. However, the dispersion of Islam could not run smoothly before Wali Songo emerged in Indonesian society at the fifteenth century. In this era, Islam could be received and absorbed widely by the Indonesians. The Islamic school of law that is brought by Wali Songo is Syafi’ite. Even most of Muslims in Indonesia follow Syafi’ite school of law, in the real life including in their daily prayers and trade activities, they are not use this school entirely. One of the reasons why this school is not practiced by Muslims fully is difficult to practice. The existence of Qaul al-Mukhtār of al-Nawawī can be an alternative way for the followers of this school of law that is difficult in practicing one of his opinions. Besides its strong arguments, Qaul al-Mukhtar of al- Nawawī is not really out from the rule of Syafi’ite school of law. In addition, it is representation of Fikih al-Muyassar (simplifed fiqh) concept for Muslim in Indonesia. Therefore, the follower of Syafi’ite school of law in Indonesia can feel easy and peace in practicing Islam.